INBOUND MARKETING IN THE HOSPITALITY INDUSTRY: A SYSTEMATIC REVIEW IN THE LAST 12 YEARS - Romero Montero, Andrés; Cely Álvarez , Adriana; Sellers Rubio, Ricardo (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2023)
This paper aims to analyze the evolution in the research of digital marketing tools and strategies used by inbound marketing in the main journals related to this term and related topics to the hospitality industry. The results obtained have led to detect a progressive increase in the number of publications analyzing inbound marketing tools in recent years (2010-2021), which point to the construction of a Marketing 5.0 paradigm. A high rotation of topics has also been detected, describing a dynamic and fluctuating research field. It is recommended that more research be carried out on inbound marketing (as a strategic model of structured marketing) to allow for an integrative vision of technologies, which until now have been analyzed without a defined backbone linked to the hotel business.